Gender differences in paediatric hospital chief executive officer compensation - Dustin D French; Heather Ballard; Mitch Phillips; Eric C Cheon (BMJ Publishing Group, 2022)
Though there is a well-established gender pay gap in medicine, studies on compensation disparities between women and men chief executive officers (CEO) showed mixed results. We conducted a cross-sectional study of children's hospitals in the USA to evaluate whether CEO gender was associated with compensation differences. Nine out of 31 children's hospitals employed a female CEO. There was no significant difference between men and women CEOs in terms of hospital characteristics (location, size or ranking in US News and World report) or CEO characteristics (advanced degrees, tenure or compensation). Gender was not associated with significant differences in CEO compensation.